Perspective of : New Chapter With New "Exposome" and "-omics" - Lu Cai (SAGE Publishing, 2024)
This is an editorial from the new editor-in-chief, EIC, who starts his role in March 2024. Due to the remarkable advance of various research fields in terms of its concepts and technology, the emerging concepts of "Exposome" and associated "Exposomics" have been introduced into the toxicology research. Therefore, the mission of "Dose-Response" will remain adhered to the original goals but will incorporate with these new concepts as the next chapter's principle and strategies. Accordingly, although it remains with special interest in the biological response to low-dose (level) ranges of stresses. The types and contents of interested manuscripts will be extended with more diverse, newer concepts from a wide range of disciplines. We wish this journal can open a door for various discipline scientists and researchers to share their state-of-the-art discoveries to shed new insight to understand the impact of environmental and toxicological medicine and develop more specific and effective intervention strategies.